Application of inter-SINE amplified polymorphism (ISAP) markers for genotyping of Cucumis melo accessions and its transferability in Coleus spp - Siti Yuli Meilanda Sormin; Aziz Purwantoro; Agus Budi Setiawan; Chee How Teo (Society for Indonesian Biodiversity, 2021)
Abstract. Sormin SYM, Purwantoro A, Setiawan AB, Teo CH. 2021. Application of inter-SINE amplified polymorphism (ISAP) markers for genotyping of Cucumis melo accessions and its transferability in Coleus spp. Biodiversitas 22: 2918-2929. An unambiguous characterization of melon (Cucumis melo L.) accessions based on their morphological traits is often laborious and affected by environment when compared with molecular marker genotyping. Short interspersed nuclear elements (SINEs) are highly abundant non-autonomous and non-coding retrotransposons that are widely scattered over all chromosomes of eukaryotes. They can serve as a good molecular marker for routine genotyping in plant breeding and marker-assisted selection. This study aimed to apply inter-SINE amplified polymorphism (ISAP) markers for genotyping of Cucumis melo accessions and its transferability in Coleus spp. Twenty-one C. melo accessions, one C. metuliferus E. Mey. ex Naudin, and 15 accessions of Coleus spp. were used for ISAP marker development. A copy of cucumber-specific long interspersed nuclear element (LINE) and multiple copies of melon-specific SINE were identified and isolated. ISAP primers were designed from the highly conserved region of the SINEs and LINE. The melon and cucumber-specific ISAP markers showed a higher degree of polymorphism (87.5%-100%) than potato ISAP markers (60%-100%) in all the tested melon accessions. The unweighted pair group method with arithmetic average (UPGMA) dendrogram generated from polymorphic ISAP bands clearly distinguish the Cucumis melo accessions from their distantly related wild species C. metuliferus. The transferable nature of Cucumis ISAP marker system was demonstrated in Coleus species, where the marker differentiates the tested accessions.